The reliability of Rickett's analysis using cephalometric tracing on Iraqi sample aged 8-10 year (Mustansiria Dental Journal, 2018)
Cephalometric radiographs were taken for (48) subjects with class I occlusion ;(25) females and (23) males , which selected on the standarization of the radiographs.Sample ages range 8-10 years . cephlometric tracing are carried out using the samepoints, lines, angles and axis of Rickett's analysis.On comparing the results of this research which is carried out on Iraqi samplewith Rickett’s analysis on Caucasian people of the same age appears that there aredifferences in most of these measurements and this due to racial factors and ethnicvariations which play a great role in differences between each ethnic group .The results of Iraqi measurements (mean values ) as fallows:-facial axis (Y-axis) =91.3°; facial depth angle =81.2° ; Frankfort-mandibular planeangle=30°; convexity of point A (mm)=2.7mm; lower incisor to A-pog =1.8mm;angle=26.1° and finally ANS-Xi-Pm angle (lower facial height) = 45.8°.